The virtual atomic and molecular data centre (VAMDC) consortium *http://www.vamdc.eu. (17th March 2016) - Dubernet, M L; Antony, B K; Ba, Y A; Babikov, Yu L; Bartschat, K; Boudon, V; Braams, B J; Chung, H-K; Daniel, F; Delahaye, F; Zanna, G Del; Urquijo, J de; et al.
Abstract: The Virtual Atomic and Molecular Data Centre (VAMDC) Consortium is a worldwide consortium which federates atomic and molecular databases through an e-science infrastructure and an organisation to support this activity. About 90% of the inter-connected databases handle data that are used for the interpretation of astronomical spectra and for modelling in many fields of astrophysics. Recently the VAMDC Consortium has connected databases from the radiation damage and the plasma communities, as well as promoting the publication of data from Indian institutes. This paper describes how the VAMDC Consortium is organised for the optimal distribution of atomic and molecular data for scientific research. It is noted that the VAMDC Consortium strongly advocates that authors of research papers using data cite the original experimental and theoretical papers as well as the relevant databases.